2021
DOI: 10.1029/2020pa004139
|View full text |Cite
|
Sign up to set email alerts
|

SST Changes in the Indian Sector of the Southern Ocean and Their Teleconnection With the Indian Monsoon During the Last Glacial Period

Abstract: The northern and the southern polar regions exhibit synchronous changes on the orbital and a coupled bipolar association on the millennial timescales (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…Climate‐sensitive geochemical proxies are important for model‐data intercomparison and cross‐validation of both simulated and reconstructed climate data (e.g., Kumar et al., 2021). Because the geochemical proxy data presented here reflects late Pliocene SoAM intensity, it is important to compare our results with simulated regional late Pliocene precipitation data sets.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Climate‐sensitive geochemical proxies are important for model‐data intercomparison and cross‐validation of both simulated and reconstructed climate data (e.g., Kumar et al., 2021). Because the geochemical proxy data presented here reflects late Pliocene SoAM intensity, it is important to compare our results with simulated regional late Pliocene precipitation data sets.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies provide time-slice simulations of climate variables during the MPWP (Dowsett et al, 2013;Haywood et al, 2013Haywood et al, , 2016, spatio-temporally resolved General Circulation Models (GCM) simulations for the entire Pliocene do not yet exist. Computational challenges in using climate models to simulate variables over an extended time frame have limited the availability of such records mostly to the last 2000 years (Tardif et al, 2019) with a few reanalyzes and model-based studies stretching up to the Last Glacial Maximum (LGM) (Kumar et al, 2021;Osman et al, 2021). In Oscillayers, benthic δ 18 O records are first merged with Community Climate System Model Version 4 LGM-model simulations (Gent et al, 2011), and then extrapolated across the Plio-Pleistocene using the δ 18 O data.…”
Section: Observation and Simulation Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar et al. (2021) estimated SST using foraminiferal Mg/Ca ratio in the southern midlatitude Indian Ocean. They also invoked the concept of tropospheric temperature gradient in explaining the Indian monsoon variability during the last deglaciation (22,000–10,000 years before present).…”
Section: Methodsmentioning
confidence: 99%
“…Chakraborty et al (2012) showed that the isotopic composition of the corals from the equatorial Pacific is sensitive to ∆TT and hence potentially useful to reconstruct the Indian summer monsoon rainfall. Kumar et al (2021) estimated SST using foraminiferal Mg/Ca ratio in the southern midlatitude Indian Ocean. They also invoked the concept of tropospheric temperature gradient in explaining the Indian monsoon variability during the last deglaciation (22,000-10,000 years before present).…”
Section: Tropospheric Temperature Gradient (∆Tt) and Its Computationmentioning
confidence: 99%